RED TIDE DETECTION USING Seawifs STANDARD CHOLOROPHYLL-a ALGORITHM IN SOUTHEAST KOREAN WATERS - Gathot Winarso (BRIN, 2012)
Cochlodinium polykrikoides red tides have occurred in summer every year at coastal waters of the South Korea. Chlorophyll-a concentration data estimated from ocean color satellite SeaWiFS (Sea-viewing Wide Field-of-view Sensor) were used to detect the red tide in this study. The high value of chlorophyll-a concentration used to detect red tide was analyzed and compared with red tide map produced by National Fisheries Research and Development Institute of Korea (NFRDI). Based on SeaWiFS data and NFRDI red tide map, it was found that high chlorophyll-a concentration of ≥ 5 mg/m3in SeaWiFS images corresponded to the red-tide occurrence with some limitations.